2011
DOI: 10.1302/0301-620x.93b10.26833
|View full text |Cite
|
Sign up to set email alerts
|

CT scan assessment of the pathway of the true lateral approach for transforaminal endoscopic lumbar discectomy

Abstract: We performed a prospective study to examine the influence of the patient's position on the location of the abdominal organs, to investigate the possibility of a true lateral approach for transforaminal endoscopic lumbar discectomy. Pre-operative abdominal CT scans were taken in 20 patients who underwent endoscopic lumbar discectomy. Axial images in parallel planes of each intervertebral disc from L1 to L5 were achieved in both supine and prone positions. The most horizontal approach angles possible to avoid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…For example, Ruetten et al [ 15 ] introduced the extreme lateral approach. Lee et al [ 10 ] reported that a true lateral approach for TELD would be possible if the patient was in the prone position, due to the ventral shift of the abdominal organs. However, the far lateral approach may increase the risk of retroperitoneal or visceral violations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ruetten et al [ 15 ] introduced the extreme lateral approach. Lee et al [ 10 ] reported that a true lateral approach for TELD would be possible if the patient was in the prone position, due to the ventral shift of the abdominal organs. However, the far lateral approach may increase the risk of retroperitoneal or visceral violations.…”
Section: Discussionmentioning
confidence: 99%
“…The exit nerve is located on the ventral side of the inter-transverse-process ligament as a leg of the safety triangle, and the ligament is appropriately dissected to identify the nerve root. It is essential to locate the nerve root in a retrograde manner and preserve the nerve root during placement of the superior pedicle screw [16], [17]. Resection of the superior articular process can fully expose the intervertebral foramen, which is located distal to the dural sac and the inferior nerve root.…”
Section: Discussionmentioning
confidence: 99%
“…The post-lateral approach involves partial resection of the lateral part of the isthmus for sufficient exposure of the disc, but the suitable range of resection has not been analyzed. [16,17] …”
Section: Introductionmentioning
confidence: 99%